Investigation of the self-talk of elite junior tennis players in a competitive setting - Boudreault, V.; Trottier, C.; Provencher, M. D. (International Journal of Sport Psychology, 2018)
This study aims to explore the content of self-talk of junior elite tennis players in relation with emotions for key events occurring during at least two matches played at a major tournament. Following a narrative inquiry strategy, semi-structured interviews were conducted with six junior elite players within 30 minutes following their last match. Data were analyzed using a thematic analysis method, revealing eight main categories of self-talk used by these athletes: (a) positive emotion expression, (b) worry, (c) rumination, (d) performance pressure, (e) disengagement, (f) motivational, (g) instructional, and (h) emotional control. Rumination and performance pressure were found to be novel emergent categories. The methodological approach employed allowed for an in-depth investigation of these elite athletes` experiences in an actual competitive setting, providing a deeper understanding of self-talk in relation to emotions. The results are discussed in reference to recent advances in the self-talk literature. Practical recommendations and avenues for future research are proposed.